METHOD FOR DETERMINING SUBJECT FOR PROSTATE BIOPSY AND DEVICE USING THE SAME - KIM JEE EUN; JUNG YU JIN; KIM HAKMIN; KIM EUNAE; KWON EUNKYUNG (2024)
The present invention relates to a method for determining a subject for a prostate biopsy and a device using the same. A method for determining a subject for a prostate biopsy according to the present invention includes the steps of: receiving a value of a subject's age at the time of the biopsy, a prostate-specific antigen density, and a prostate cancer genetic risk score; inputting the value of the subject's age at the time of the biopsy, the prostate-specific antigen density, and the prostate cancer genetic risk score into a logistic regression model to derive a probability of prostate cancer of the subject as a value between 0 and 1; and comparing the derived value between 0 and 1 with a reference value to determine whether the subject requires a prostate biopsy, wherein the prostate-specific antigen density is a value obtained by dividing the serum prostate-specific antigen level (serum PSA level (mg/dl)) by the total prostate volume (cc), and the prostate cancer genetic risk score is calculated by assigning individual weights to each genetic mutation information. 본 발명은 전립선 조직 검사 대상자를 판별하는 방법 및 이를 이용한 장치에 관한 것이다. 본 발명에 따른 전립선 조직 검사 대상자를 판별하는 방법은 피검자의 조직검사 당시 연령, 전립선 특이항원 밀도 및 전립선암 유전위험점수의 수치를 입력받는 단계, 상기 입력된 피검자의 조직검사 당시 연령, 전립선 특이항원 밀도, 전립선암 유전위험점수의 수치를 로지스틱 회귀 모델에 입력해 상기 피검자의 전립선 암 확률을 0 내지 1 사이의 값으로 도출하는 단계 및 상기 도출된 0 내지 1사이의 값을 기준값과 비교해 상기 피검자의 전립선 조직 검사 필요 여부를 판단하는 단계를 포함하고, 상기 전립선 특이항원 밀도는 혈청 전립선 특이항원 수치(Serum PSA level(mg/dl))를 총 전립선 부피(Total prostate volume (cc))로 나눈 값이고, 상기 전립선암 유전위험점수는 각 유전 변이 정보에 개별적인 가중치를 부여하여 계산한 것을 특징으로 한다.